Canada : Financial Sector Assessment Program-Intensity and Effectiveness of Federal Bank Supervision in Canada-Technical Note. (IMF Staff Country Reports; Country Report ;, 2014)
This paper evaluates Financial Sector Assessment Program (FSAP) intensity and effectiveness of Federal Bank supervision in Canada. The IMF report highlights that a key element of effective supervision is a willingness to increase supervisory pressure promptly when a supervisor identifies weaknesses in an institution. The IMF funding for Canadian banks is primarily through deposits and lending focuses on traditional bank products in Canada in the personal and commercial sectors. It also highlights that one of the key characteristics of Canada is a government housing policy that has contributed to a very safe and liquid residential mortgage finance system.